Evaluation of the coupling coordination effect of Hefei Rail transit station area based on supply and demand matching - Wangyang Gui; Mengnan Cheng; Tong Zhang; Yifei Guo; Bin Xu (PLoS ONE, 2025)
The coupling of supply and demand in the rail transit station area is an important driving force for ensuring the balanced development between the traffic functions and the place performance of the rail transit station area. This study evaluates the development status of these two aspects in each rail transit station area explores the possibility of combining the TOD (Transit-Oriented Development) model with the concept of the 15-minute city, and focus on the importance of TOD planning and its optimization strategies, this paper takes 44 rail transit station areas within the Second Ring Road of Hefei City as examples. Through multi-source data, a “supply-demand” coupling coordination degree model is constructed to evaluate the matching status between the needs of “people” and the supply of facilities and resources in the rail transit station area, and analyze the influence mechanism of the allocation of public service resources in different communities on the rail transit station area, thus constructing a comprehensive analysis framework and practical guidelines for modern urban planning. For the station areas with poor coupling coordination of supply and demand, references are provided for urban planning from four dimensions: the construction of the planning reference framework, the scientific nature of the early-stage site selection, the dynamic adjustment of the mid-term monitoring, and the refinement of the later-stage governance, which is of great significance for promoting the comprehensive development and sustainable development of the areas surrounding the rail transit stations.